Treatment of Direct Payment Systems for Multiple Recipients on Payment Error Rates in Central Government Agencies Located in Palu City, Central Sulawesi - DAMAYANTI, Dita Zaskia; TOTANAN, Chalarce; ZAHRA, Femillia; PAKKAWARU, Muhammad Ilham (Journal of Governance, Taxation and Auditing, 2024)
This study aims to understand the treatment mechanisms carried out by government institutions located in the Palu City area of Central Sulawesi when payment errors occur using the direct payment system. The object of this research is the procedures followed when payment errors arise through the direct payment system in companies located in Palu City, Central Sulawesi. This study uses a qualitative research method with a descriptive approach. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words obtained from a case study by conducting detailed observation of the research object at the Class II Agricultural Quarantine Office in Palu. The type of data used in this study is primary data. Data collection methods used in this study include interviews and documentation. The target respondents consist of planning officers, expenditure treasurers, revenue treasurers, state property officials, commitment-making officers, personnel officers, and all employees. It was found that payment errors occur when there is a discrepancy in the inputted data in the system, causing the payment to not be received by the intended recipient. The company’s treatment includes modifying and correcting the recipient data according to procedures established by the Directorate General of Treasury and the relevant institution through several steps. The findings of this study have implications regarding the treatment of direct payment systems for multiple recipients in relation to payment errors in government agencies.